Kajian Persepsi Siswa SMAN 5 Malang terhadap Pembelajaran berbasis Proyek dengan Sumber Belajar TPA Supit Urang Malang - Dwida Maghfiroh; Herawati Susilo; Ibrohim Ibrohim (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
This study aims to know the students of SMAN 5 Malang perceptions based on project-based learning with TPA Supit Urang Malang learning resources. This research is descriptive quantitative. The sample in this research are the students of class X MIA 7 SMAN 5 Malang academic year 2015/2016 which consisting of 33 students. The instruments in this research is the students’ perception questionnaire sheet consisting of 26 items assessment indicators. The indicator assessment include students' perception of learning materials, learning models, learning resources, handouts, and worksheets. Research results seen that the percentage of students' perception of learning materials is 97,5%, learning models is 97,5%, learning resources is 97,5%, handouts is 95,0%, and worksheets is 95.0%. Based on the percentage gained an average of 96.50% indicating that perception of the students are very good or very effective. Students feel happy and interested during the project-based learning with TPA Supit Urang Malang learning resources. Key Words : Perception, SMAN 5 Malang, project-based learning, TPA Supit Urang Malang